Protective Effect of Piceatannol Against Acute Lung Injury Through Protecting the Integrity of Air-Blood Barrier and Modulating the TLR4/NF-κB Signaling Pathway Activation - Peng, Lu-Yuan; Yuan, Meng; Shi, Hai-Tao; Li, Jing-He; Song, Ke; Huang, Jiang-Ni; Yi, Peng-Fei; Fu, Ben-Dong; Shen, Hai-Qing (Frontiers in Pharmacology, 2020)
Acute lung injury (ALI) is a common and complex inflammatory lung syndrome with higher morbidity and mortality rate. Piceatannol (PIC) has anti-inflammation and anti-oxidant properties. The study was designed to explore the effect and the action mechanisms of PIC on lipopolysaccharide (LPS)-induced ALI. Twenty-four hours after LPS challenge, mice from different treatment groups were euthanized, and the bronchoalveolar lavage fluid (BALF) and lung tissue samples were collected. Then the degree of pulmonary edema, lung pathological changes, myeloperoxidase (MPO) activity, and the production of pro-inflammatory cytokines were detected. Additionally, the messenger RNA (mRNA) expressions associated with cell adhesion molecules and tight junction were analyzed through quantitative real-time (qRT)-PCR, and the TLR4/NF-κB activation was examined by western blot. The results showed that PIC significantly inhibited LPS-induced lung edema, histopathological damage, MPO activity, cell infiltration, and pro-inflammatory cytokines production. Moreover, PIC notably suppressed mRNA expressions associated with inflammation and cell adhesion molecules. Furthermore, PIC also alleviated LPS-induced damage of air-blood barrier through reducing the levels of total proteins in BALF and recovering the expression of occludin and ZO-1 in the lung tissues. We also found that PIC remarkably restrained the LPS-induced TLR4/NF-κB pathway activation in lung tissues. In conclusion, PIC may be potential to treat LPS-induced acute lung injury (ALI) via regulating air-blood barrier and TLR4/NF-κB signaling pathway activation.